Batryticatus Bombyx Protects Dopaminergic Neurons Against MPTP-Induced Neurotoxicity by Inhibiting Oxidative Damage - Hye-Sun Lim; Joong-Sun Kim; Byeong Cheol Moon; Seung Mok Ryu; Jun Lee; Gunhyuk Park (Antioxidants, 2019)
Oxidative stress plays an important role in the degeneration of dopaminergic neurons in Parkinson’s disease (PD). Altered redox homeostasis in neurons interferes with several biological processes, ultimately leading to neuronal death. Oxidative damage has been identified as one of the principal mechanisms underlying the progression of PD. Several studies highlight the key role of superoxide radicals in inducing neuronal toxicity. Batryticatus Bombyx (BB), the dried larva of Bombyx mori L. infected by Beauveria bassiana (Bals.) Vuill., has been used in traditional medicine for its various pharmacological effects. In the present study, BB showed a beneficial effect on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced neurotoxicity by directly targeting dopaminergic neurons. Treatment with BB improved behavioral impairments, protected dopaminergic neurons, and maintained dopamine levels in PD mouse models. Here, we investigated the protective effects of BB on MPTP-induced PD in mice and explored the underlying mechanisms of action, focusing on oxidative signaling. In MPTP-induced PD, BB promoted recovery from impaired movement, prevented dopamine depletion, and protected against dopaminergic neuronal degradation in the substantia nigra pars compacta (SNpc) or the striatum (ST). Moreover, BB upregulated mediators of antioxidative response such as superoxidase dismutase (SOD), catalase (CAT), glutathione (GSH), Heme oxygenase 1 (HO-1), and NAD(P)H (nicotinamide adenine dinucleotide phosphate) dehydrogenase (NQO1). Thus, treatment with BB reduced the oxidative stress, improved behavioral impairments, and protected against dopamine depletion in MPTP-induced toxicity.